2011
DOI: 10.1037/a0023359
|View full text |Cite
|
Sign up to set email alerts
|

Minority stress and college persistence attitudes among African American, Asian American, and Latino students: Perception of university environment as a mediator.

Abstract: We examined whether perception of university environment mediated the association between minority status stress and college persistence attitudes after controlling for perceived general stress. Participants were 160 Asian American, African American, and Latino students who attended a predominantly White university. Results of a path model analysis showed that university environment was a significant mediator for the association between minority status stress and college persistence attitudes. Additionally, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
88
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 61 publications
5
88
1
2
Order By: Relevance
“…While there is evidence that the experience of psychological distress is negatively related to college students' grade point average and degree completion (Eisenberg, Golberstein, & Hunt, 2009), only one study was located that examined the relation of ethnic minority status stress to college persistence. Wei et al (2011) reported that minority status stress was negatively related to persistence expectations among a mixed group of Asian American and Hispanic college students.…”
Section: Consuelo Arbona 13mentioning
confidence: 99%
See 1 more Smart Citation
“…While there is evidence that the experience of psychological distress is negatively related to college students' grade point average and degree completion (Eisenberg, Golberstein, & Hunt, 2009), only one study was located that examined the relation of ethnic minority status stress to college persistence. Wei et al (2011) reported that minority status stress was negatively related to persistence expectations among a mixed group of Asian American and Hispanic college students.…”
Section: Consuelo Arbona 13mentioning
confidence: 99%
“…Several studies have shown that when controlling for normative college stressors, minority stress is uniquely associated to ethnic minority college students' psychological and academic adjustment (e.g. Arbona & Jimenez, 2014;Rodriguez, Myers, Morris, & Cardoza, 2000;Smedley et al, 1993;Wei et al, 2010;Wei, Ku, & Liao, 2011).…”
mentioning
confidence: 99%
“…They found that for students of colour, observing and encountering racism increased their stress levels and decreased their positive feeling about the campus climate, ultimately leading to attrition. Numerous other studies have found that an unwelcoming campus racial climate is associated with feelings of isolation, students' feeling less committed to the institution, and higher rates of attrition for students of colour (Griffin et al, 2012;Hurtado & Carter, 1997;Solórzano et al, 2000;Wei, Ku & Liao, 2011). An interesting study by Griffin et al (2012) explored the role of campus racial climate in Graduate Diversity Officers' ability to recruit and retain a diverse group of doctoral students.…”
Section: Campus Racial Climatementioning
confidence: 97%
“…The term, "first-generation," can be somewhat ambiguous within academic discourse. Wei, Ku, and Liao (2011) define first-generation students as minority students "who were born in another country" (p. 197). The National Center for Educational Statistics (2005) defines first-generation status as "students who are the first members of their families to attend college" (p. iii).…”
mentioning
confidence: 99%
“…However, despite the author's rigorous methodology, some concerns still remained unaddressed. For instance, it is clear that the stress experienced by minorities (and arguably first-generation students) is different than the stress experienced by the dominant culture at a predominately White university (Wei, Ku, & Liao, 2011). However, I would argue that part of going to college is learning how to adapt to new situations.…”
mentioning
confidence: 99%